In Vivo Antidiabetic Potential Test of Suruhan’s (Peperomia pellucida) Purified Extract Using Alloxan-Induced Wistar Rats - Sa'ad, Muhammad; Kusuma, Eka Wisnu; Susanti, Ira; Handayani, Dewi Uthamy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Natural-based antidiabetic drugs need to be developed as an alternative to synthetic antidiabetic drugs to minimize side effects. Suruhan extract (Peperomia pellucida) is one of the natural ingredients that has antidiabetic activity. In vitro studies show that ethanol extract, hexane extract and purified ethanol extract have antidiabetic effectiveness. This study was conducted to test the antidiabetic activity of purified suruhan extract on alloxan-induced Wistar rats to confirm antidiabetic activity in vivo. A total of 8 test groups, each consisting of 3 rats induced by alloxan 125mg/KgBW and non-fasting blood glucose was checked at 0; 30; 60; 90; 120; and 150 minutes using a glucometer, then the percentage of decrease in blood glucose levels was calculated. Positive control using glibenclamide 0.45mg/KgBW, negative control using CMC-Na 0.5%. The treatment groups consisted of: Extract 20mg/KgBW (E20); Extract 40mg/KgBW (E40); Extract 80mg/KgBW (E80); Purified Extract 20mg/KgBW (P20); Purified Extract 40mg/KgBW (P40); and Purified Extract 80mg/KgBW (P80). Results showed the percentage decrease in blood glucose levels of E20; E40; E80; P20; P40; and P80 respectively: 39.93%; 42.29%; 46.93%; 38.34%; 55.34%; and 66.40%. The percentage decrease in blood glucose levels of the positive control group was 53.71%. The Purified Extract treatment groups of 40mg/KgBW and 80mg/KgBW showed the percentage decrease in blood glucose levels equivalent to and better than the positive control of glibenclamide 0.45mg/KgBW (p<0.05%). The purified extract was shown to have antidiabetic effects in vivo and is promising for use as an alternative antidiabetic drug.